Sierra Leone’s Constitutional Framework for Resource Governance and Economic Inequality: A Socio-Legal Study - Thomas Sheku Marah (IAIN Bone, 2026)
This article examines why Sierra Leone has not fully translated its mineral wealth and post-conflict legal reforms into equitable and sustainable development outcomes. It argues that the problem cannot be explained solely by the resource curse thesis or by the absence of legal reform, but by the interaction between constitutional non-justiciability, statutory ambition, institutional capacity, and local political-economic asymmetries. Employing doctrinal legal analysis complemented by a socio-legal institutional perspective, the article analyses the Constitution of Sierra Leone 1991, the Mines and Minerals Development Act, 2022 (Act No. 16 of 2023), and relevant academic, policy, and institutional materials. The findings show that the Constitution provides important normative commitments to welfare, social justice, equality of opportunity, and the public use of natural resources, but the non-justiciability of the Fundamental Principles of State Policy limits their direct enforceability. The 2022 Act partially responds to this constitutional enforceability gap by strengthening Community Development Agreements, revenue-linked benefit-sharing mechanisms, transparency obligations, and environmental and social safeguards. However, these statutory mechanisms have not yet demonstrably produced commensurate distributive outcomes because their effectiveness remains constrained by weak regulatory capacity, uneven enforcement, informality in artisanal and small-scale mining, risks of elite capture, and unequal community participation. The article conceptualises this condition as a legalised distributive deficit, in which law formally recognises transparency, participation, benefit-sharing, and environmental protection while remaining unable to secure material redistribution without institutional enforcement, regulatory autonomy, and meaningful community accountability.